The Effect Of Drill and Imitation Techniques in Students’ Ability in Using English Intonation Of Grade VIII Students of SMP Negeri 8 Pematangsiantar - Damanik, Hasan (The Explora, 2021)
This study attempted to find out (1) the effect of conventional technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation; (2) the effect of imitation technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation; (3) the effect of drill technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation; (4) the effect of drill technique more significant than the effect of imitation technique or than the effect of conventional technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation. This study was conducted by using experimental research. The population of the study was all classes of grade eight in 2015/2016 academic year at SMP Negeri 8 Pematangsiantar. There are two classes were chosen as the sample of the research by applying random sampling technique. Each class consists of 34\ students. The instrument used for the data collection was a test. The data were analyzed by using ANOVA. The research finding showed that (1) the effect of conventional technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation is not more significant that is shown by the following students’ score: mean = 49.11, maximum score = 60, minimum score = 40; (2) the effect of imitation technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation is shown by the following students’ score: mean = 61,76, maximum score = 85, minimum score = 45; (3) the effect of drill technique to the ability of grade VIII students of SMP N 8 Pematangsiantar in the English intonation is shown by the following students’ score: mean = 75,58, maximum score = 90, minimum score = 50; (4) the effect of Drill technique more significant than the effect of imitation technique or than the effect of conventional technique to the ability of gradeVIII students of SMP N 8 Pematangsiantar in the English intonation.